Grasshopper optimization algorithm scaled fractional order PI-D controller applied to reduced order model of load frequency control system. (3rd May 2020) - Guha, Dipayan; Roy, Provas Kumar; Banerjee, Subrata
ABSTRACT: An effort has been given to derive the reduced-order models (ROMs) of higher-order power systems using model-order reduction techniques. Fractional-order proportional-integral-derivative (FOPI-D) controller is designed and incorporated in the models to cope up the load perturbation and to provide adequate damping to the system oscillation. To avoid the set-point kick problem of PID controller, the derivative action is considered in the feedback path that results in PI-D controller. Grasshopper optimization algorithm (GOA) has been used to optimize the FOPI-D controller gains. To affirm tuning competence of GOA, the convergence mobility of the GOA is compared with some well-known optimization techniques. The analysis of the system responses carried out in this work demonstrates that the controller design effort is significantly reduced with the derived ROMs, and confirms the matching of time and frequency responses with the higher-order system. To quantify the efficacy of FOPI-D controller, the closed-loop responses are compared with some conventional and intelligent controllers. From the presented result, substantial improvements in the system dynamics are observed with GOA: FOPI-D controller in normal circumstances as well as in the presence of system uncertainties. The success of GOA: FOPI-D controller is also confirmed for a hybrid energy distributed power system.